2021
DOI: 10.1111/resp.14066
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognostic impact of physical frailty in interstitial lung disease: A prospective cohort study

Abstract: Background and objective: Physical frailty is associated with increased mortality and hospitalizations in older adults. We describe the prevalence of physical frailty and its prognostic impact in patients with a spectrum of fibrotic interstitial lung disease (ILD). Methods: Patients with fibrotic ILD at the McMaster University ILD programme were prospectively followed up from November 2015 to March 2020. Baseline data were used to classify patients as non-frail (score = 0), pre-frail (score = 1-2) or frail (sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 29 publications
(34 reference statements)
2
28
0
Order By: Relevance
“…This correlates with Guler et al study which show a higher fat mass in ILD individuals with more impaired pulmonary function. 48 These muscular composition alterations are particularly interesting considering there is a considerable overlap between frailty and muscle alterations 42 that our data seem to confirm in ILD frail patients. The loss of muscle function and mass as well as alteration of muscle composition occur with ageing 43 and in other respiratory chronic disease, such as COPD.…”
Section: Muscles Function and Compositionsupporting
confidence: 64%
See 1 more Smart Citation
“…This correlates with Guler et al study which show a higher fat mass in ILD individuals with more impaired pulmonary function. 48 These muscular composition alterations are particularly interesting considering there is a considerable overlap between frailty and muscle alterations 42 that our data seem to confirm in ILD frail patients. The loss of muscle function and mass as well as alteration of muscle composition occur with ageing 43 and in other respiratory chronic disease, such as COPD.…”
Section: Muscles Function and Compositionsupporting
confidence: 64%
“…It is thus reassuring that the group of patient is similar to previously published data both for their clinical and respiratory status and for their frailty status distribution. 48 In addition, since the control participants were recruited via our research center data bank, we are aware of a possible social participation bias explaining the high performance of our control group for respiratory function and functional exercice capacity. However, in regard with the huge magnitude of the between-groups (ILD vs. healthy subjects) values, the authors are confident that the observed differences were only slightly altered by this potential bias and that the impairments described in the present study are well present in ILD patients when compared to healthy subjects of comparable age, sex and BMI.…”
Section: Methodological Considerations and Study Limitationmentioning
confidence: 99%
“…The reasons for reduction in mortality are unclear, whether it is related to smoking rates, earlier diagnosis, management, frailty levels or environmental/geographic factors remains to be seen. 60,61 Cutting et al demonstrated that patient-reported family history of fibrosis predicts reduced survival in both IPF and non-IPF ILD, indicating that a positive family history should be considered in prognosticating risk. 62 Additionally, Lee et al reported that the risk of several cancers in IPF is increased, with a significant risk of lung cancer (hazard ratio 5.89), thus demonstrating the need for clinicians to consider this risk when managing IPF.…”
Section: Disease Progression and Mortalitymentioning
confidence: 99%
“…They reported that from 2004 to 2017 the age‐adjusted mortality of males with IPF reduced by 4.1% from 75.5 deaths per million to 72.4 deaths and this was decreased in females by 13.4%. The reasons for reduction in mortality are unclear, whether it is related to smoking rates, earlier diagnosis, management, frailty levels or environmental/geographic factors remains to be seen 60,61 . Cutting et al demonstrated that patient‐reported family history of fibrosis predicts reduced survival in both IPF and non‐IPF ILD, indicating that a positive family history should be considered in prognosticating risk 62 .…”
Section: Diagnosis and Prognosticationmentioning
confidence: 99%
“…Milne et al have pointed out that frailty is highly prevalent in ILD patients [ 2 ]. Frailty and sarcopenia result in a loss of functional independence, where sarcopenia may be a risk factor for frailty [ 3 , 4 ]. Sarcopenia has been defined as a progressive and generalized skeletal muscle disorder that involves the accelerated loss of muscle mass and function, and increased adverse outcomes including falls, functional decline, frailty, and mortality [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%